Colonoscopies in Australia – how much does the National Bowel Cancer Screening Program contribute to colonoscopy use? - Joachim Worthington; Emily He; Jie-Bin Lew; James St John; Christopher Horn; Paul Grogan; Karen Canfell; Eleonora Feletto (Public Health Research & Practice, 2023)
Objectives and importance of study: Colorectal cancer (CRC) is Australia’s fourth most commonly diagnosed cancer. CRC screening is an effective intervention to reduce this burden. The National Bowel Cancer Screening Program (NBCSP) provides 2-yearly immunochemical faecal occult blood tests (iFOBTs) to Australians aged 50–74 years; a diagnostic colonoscopy is conducted after a positive iFOBT. Clinical guidelines inform colonoscopy usage, and appropriate use of these guidelines is vital to investigate gastrointestinal symptoms, detect bowel abnormalities and CRC, and remove precancerous polyps.